The mediating roles of social benefits and social influence on the relationships between collectivism, power distance, and influenza vaccination among Hong Kong nurses: A cross-sectional study. (November 2019) - Li, Kin-Kit; Chan, Michael Wing Ho; Lee, Shui Shan; Kwok, Kin On
Abstract: Background: Despite being recommended by many medical organizations, the uptake rates of seasonal influenza vaccination among healthcare workers, including nurses, are still unsatisfactory. Considering the impact of cultural values on organizational behaviors, vaccination among nurses may also be influenced by cultural values via their impacts on socially oriented motivation and the acceptance of social influence. Objectives: This study examined whether and in what way two individual-level cultural dimensions, collectivism and power distance, would influence vaccination via social benefits (i.e., self-and-clan protection and community protection) and social influence (i.e., authority advice, and family-and-peer advice), respectively, among nurses. Design: A cross-sectional online survey. Setting: An invitation to participate in the survey was sent to nurses using the contact list of a professional nursing organization in Hong Kong and by personal referrals. Participants: A total of 1386 nurses (mean age = 37.82, SD = 10.36; 89% women) completed the survey. Methods: The survey included instruments on cultural values, perceived social benefits, and social influence, and questions regarding 2-year vaccination records. The mediation model was tested using structural equation modeling with bootstrapped samples. Subgroup analyses were conducted to examine whether the mediation paths were different across different levels of demographic factors. Results: The structural paths in the mediation model were different between nurses that had been vaccinated in the past and those who had not. In the adoption model (i.e., for nurses non-vaccinated in the past), the positive effects of collectivism on vaccination were mediated by self-and-clan protection and authority advice, whereas the negative effect of collectivism on vaccination was mediated by community protection. In addition, the positive effect of power distance on vaccination was mediated by authority advice. In the maintenance model (i.e., for nurses vaccinated in the past), except for the positive effect of collectivism on vaccination via authority advice, the other indirect effects were not significant. The direct effect of collectivism on vaccination was negative, whereas the direct effect of power distance on vaccination was positive. Conclusions: Collectivism and power distance may guide how nurses attend to and process social information and subsequently influence their vaccination adoption behaviors. More research is needed to examine how cultural dimensions may influence vaccination maintenance and the applicability of the current findings to other cultures.